4t+3d=9

Simple and best practice solution for 4t+3d=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t+3d=9 equation:


Simplifying
4t + 3d = 9

Reorder the terms:
3d + 4t = 9

Solving
3d + 4t = 9

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-4t' to each side of the equation.
3d + 4t + -4t = 9 + -4t

Combine like terms: 4t + -4t = 0
3d + 0 = 9 + -4t
3d = 9 + -4t

Divide each side by '3'.
d = 3 + -1.333333333t

Simplifying
d = 3 + -1.333333333t

See similar equations:

| 8x-11=-9 | | 18x^2-(3x-2)(6x-1)=-17 | | F(X)=x^2-48 | | 4=2a-6 | | s=-1s | | (x+1)[2x+1]=x+0.5(1)+1.000000001 | | (x+1)[2x+1]=x+0.5(1) | | (x+1)[2x+1]=x+0.5 | | (x+1)[2x+1]=x+0.25 | | (9-6i)*m=9-6i | | (x+1)[2x+1]=x | | (9-6i)*m=m | | m=6/m | | x=0x | | 60=x-134 | | 8x^2-35x-38=0 | | (2x+3)(2x+3)+2x-3(2x-3)=(4x+6) | | 3(2x+8)=5(4x-6) | | Log(13)+log(15)=log | | ln(x+4)=1 | | 6*7-2=x | | 0.75(4x-1)=0.25(6x-1) | | 9-5(n+6)=32 | | 42-m=2m-3 | | D^4+5d^3+6D^2-4D-8=0 | | (D^4+5d^3+6D^2-4D-8)y=0 | | 4cosx^4-cosx^2+1=0 | | 5(4+x)-1=2(x+10)-4x | | 4x=120-2x | | 3x+2x=160 | | 800x=20 | | 21-x=67 |

Equations solver categories